2014
DOI: 10.1039/c3cs60206k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic aspects of dinitrogen cleavage and hydrogenation to produce ammonia in catalysis and organometallic chemistry: relevance of metal hydride bonds and dihydrogen

Abstract: Dinitrogen cleavage and hydrogenation by transition-metal centers to produce ammonia is central in industry and in Nature. After an introductory section on the thermodynamic and kinetic challenges linked to N2 splitting, this tutorial review discusses three major classes of transition-metal systems (homogeneous, heterogeneous and biological) capable of achieving dissociation and hydrogenation of dinitrogen. Molecular complexes, solid-state Haber-Bosch catalytic systems, silica-supported tantalum hydrides and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
575
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 687 publications
(579 citation statements)
references
References 57 publications
1
575
0
3
Order By: Relevance
“…Consequently, the extent of electron donation into the N 2 unit may vary with the metals and their oxidation states resulting either in a weak activation of the N-N triple bond or in the reduction to a double bond (N 2 2-) or even to a N-N single bond (N 2 4-). [38][39][40]42,44,46,47,51,52] A few experimental studies showed that a cooperative N 2 activation may even lead to complete N-N bond cleavage. [53][54][55] Notably, iron (a late metal) is present in all three nitrogenase enzyme types, and also the industrial Haber-Bosch process uses iron-based catalysts for N 2 reduction.…”
Section: Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the extent of electron donation into the N 2 unit may vary with the metals and their oxidation states resulting either in a weak activation of the N-N triple bond or in the reduction to a double bond (N 2 2-) or even to a N-N single bond (N 2 4-). [38][39][40]42,44,46,47,51,52] A few experimental studies showed that a cooperative N 2 activation may even lead to complete N-N bond cleavage. [53][54][55] Notably, iron (a late metal) is present in all three nitrogenase enzyme types, and also the industrial Haber-Bosch process uses iron-based catalysts for N 2 reduction.…”
Section: Special Issuementioning
confidence: 99%
“…Most of the model systems in the literature are based on mid to early transition metals (group 4-6), which were found to effectively activate coordinated dinitrogen, leading to N 2 complexes with weaker, and thus longer N-N bonds as compared to corresponding complexes of the late transition metals (groups [8][9][10]. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] This is due to the fact, that backbonding to the π* orbitals of the N 2 ligand depends on the energetic positioning of the d orbitals relative to the NNπ* orbitals, which is favorable for low-valent, electropositive metals, and more unfavorable for late metals. Consequently, the extent of electron donation into the N 2 unit may vary with the metals and their oxidation states resulting either in a weak activation of the N-N triple bond or in the reduction to a double bond (N 2 2-) or even to a N-N single bond (N 2 4-).…”
Section: Special Issuementioning
confidence: 99%
“…In this context, most of the effort has been focused on molybdenum and iron systems [14][15][16][17][18]. Two major strategies for catalytic N2 activation by homogeneous systems were developed: reductive protonation to yield ammonia and reductive silylation to yield silylamines ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…There are reviews on transition metal N2 activation which cover N2 binding modes [27][28][29], multimetallic N2 activation [30,31], the relevance of metal hydride complexes to N2 activation [32,33], N2 cleavage and functionalisation [34,35] (including electrochemical [36] and photolytic N2 cleavage [37]), and N2 activation at bare metal atoms [38] and using surface organometallic chemistry [39]. Specific reviews have also focused on activation by group 4 metals [40][41][42], iron [31,43,44], molybdenum [24,[45][46][47], and the mid-to-late transition metal centres [48].…”
Section: Open Accessmentioning
confidence: 99%